Epidemiology of spinal injury patients admitted to the department of orthopaedics, King George Medical University - Kumar, Satyendra; Verma, Vikas; Sharma, Vineet; Singh, Shailendra (International Journal of Research in Orthopaedics, 2019)
Background: Socioeconomic structure, policies and cultural traditions play important roles in the determining the epidemiological characteristics of spinal injury patients. An understanding of epidemiology of spinal injuries is essential for planning and implementation of preventive measures as well as clinical services. The objective of this study is to describe the epidemiology of spinal injury patients admitted to the Department of Orthopaedics, King George Medical University (KGMU). Methods: Age, sex, time since injury to admission, site of injury, mechanism of injury, stability of injury, vertebral level, collision type, visibility, type of road, associated injuries, complications and outcome at the end of hospital stay was recorded. Results: Mean age of the 149 enrolled patients was 33.62±13.47 years. Male to female ratio was 2.63. More than fifty percent (52.3%) patients were admitted more than 48 hrs after injury. Most of the patients sustained injury in the house (59.1%). Falls were the most common mechanism of injury (79.2%). 54.23% of the falls were less than body height. Stable injuries (51%) were more common than unstable injuries. 21.48% patients had multiple levels of injury. 1st lumbar vertebra was the most common vertebra injured (20.88%). Ninty six (64.42%) patients had associated injuries. Most common complication were pulmonary (16.10%). Conclusions: Traumatic spinal injuries predominantly involve young males. Household falls are the most common cause of traumatic spinal injuries. There is a need to determine the modifiable factors that contribute to household falls. There is a significant association between falls and complete injuries.